Combinatorics an introduction - Faticoni, Theodore G. (Wiley, 2013)
"This book provides a treatment of counting combinatorics that uniquely includes detailed formulas, proofs, and exercises and features coverage of derangements, elementary probability, conditional probability, independent probability, and Bayes' Theorem. Using elementary applications that never advance beyond the use of Venn diagrams, the inclusion/exclusion formula, the multiplication principal, permutations, and combinations, Combinatorics is perfect for courses on discrete or finite mathematics--or as a reference for anyone who wants to learn about the various applications of elementary combinatorics"--Provided by publisher.